VLAN-Based Network Optimization as Mechanism of Improving Data Security and Performance - Fais Abubakar Bafana; Murhadi Murhadi; Dewi Chirzah; Batchuluun Yembuu; Hasan Jali (Unversitas Muhammadiyah Mataram, 2026)
Nowadays in the digital world, organizations like schools need strong network systems to help them work smoothly. Pondok Pesantren Darul Hikmah Kutoarjo Islamic School had some problems with its old network setup. These included data being shared between different parts of the school, too much broadcast traffic, and slower performance because of network conflicts. This study focuses on improving the network by using VLAN technology, which is simulated with Cisco Packet Tracer. The research uses a qualitative approach, including direct observation and reviewing existing literature. The findings show that VLANs can separate data traffic between different groups, like teachers, students, and visitors, without needing extra hardware. Testing the system showed big improvements in performance. The maximum delay went down from around 200 ms to just 10 ms, and the network became more stable by reducing jitter.